IMPLEMENTASI MODEL GEQUAMO TERHADAP UJI KUALITAS APLIKASI PARIWISATA “SUMBER GEMPONG APPS” MENGGUNAKAN METODE EUCLIDEAN DISTANCE - Nurul Fikri Sabili; Muzaka Najih; Yovi Andhika Rohma; Mohammad Fikry Fauzi; Rani Purbaningtyas (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Abstract. The advancement of digital technology has encouraged the utilization of mobile applications to support public services, including in the tourism sector. Sumber Gempong Apps is designed to facilitate tourists in accessing tourism information, booking tickets, reserving homestays, and viewing the prices of attractions and local MSME products. This study aims to evaluate the quality of the application using the GEQUAMO model and the Euclidean Distance method. The evaluation focuses on two main aspects: functionality and usability. The research employs a quantitative approach with a Likert scale questionnaire based on the indicators in the GEQUAMO model. Data were collected from users of the application and analyzed using the Euclidean Distance formula to measure the closeness between actual user scores and ideal values. The analysis results show a Euclidean distance of 0.38 for functionality and 0.47 for usability. These values indicate that the application’s quality is in the